Principal's Leadership Style Correlation With Improved External Quality Assurance System: Korelasi Gaya Kepemimpinan Kepala Sekolah Dengan Peningkatan Sistem Penjaminan Mutu Eksternal - Churahman, Taufik (Halaqa: Islamic Education Journal, 2022)
Principal leadership in educational institutions has a fairly heavy responsibility, as leaders are required to have the ability in the field of management, and motivate to improve quality results. But not a few of the principals who experience obstacles in managing it and affect the quality of the school. This article attempts to identify the principal's leadership style towards the school's external quality assurance system. The method used is a systematic literature review, namely by documenting and reviewing all articles related to the principal's leadership style and external quality assurance system. Researchers searched for data using journal articles, found as many as 27 articles between 2015-2021 in Google Scholar, Research Gate, SINTA, JAMP, and Academia. The results show that the success of an educational institution is determined by the role of its leader, democratic, innovative, effective, dynamic, and transformational leadership styles can improve the school's external quality assurance system.